Family ties and intergenerational relationships in European families in the twentieth century - Marećkova, Marie (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
Intergenerational family relationships still performed an important social function in rural society in Europe at the beginning of the twentieth century. The situation within the Czech family illustrates the current problems in family ties and intergenerational relationships that have surfaced since the nineteen nineties. Negative developmental trends are being seen, particularly in comparison with family circumstances in other European countries, most significantly the continuing ageing of the population and the wide-ranging activities of seniors. Looser relationships with their families and a decline in their engagement in caring for their grandchildren mean that Czech grandparents tend to rank alongside more socially developed countries in this respect. Under Czech conditions, however, this can lead to great strain on the active roles played by seniors. The growing number of adult offspring, particularly men, living with their parents is a far from progressive trend in social and economic development, and corresponds more closely with southern European traditions.
Keywords: kinship ties; rural society; elderly people; professional mobility; nuclear family; welfare state; cisis; center of security